2005
DOI: 10.1124/mol.104.010637
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-Induced Interactions between Angiotensin AT1and Epidermal Growth Factor Receptors

Abstract: In rat hepatic C9 cells, angiotensin II (Ang II)-induced activation of angiotensin type 1 (AT 1 ) receptors (AT 1 -Rs) stimulates extracellular signal-regulated kinase (ERK) 1/2 phosphorylation via transactivation of the endogenous epidermal growth factor (EGF) receptor (EGF-R) by a protein kinase C (PKC) ␦/Src/Pyk2-dependent pathway. This leads to phosphorylation of the EGF-R as well as its subsequent internalization. On the other hand, EGF-induced activation of the EGF-R in C9 cells was found to cause phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 39 publications
(52 reference statements)
5
64
0
Order By: Relevance
“…The AT1 receptor in turn transactivates EGF receptor, which leads to activation of multiple downstream effectors such as Ras-ERK and PI3-K. In this regard, caveolin-1 appears to serve a scaffold forming a large signalplex, which includes AT1 receptor, EGF receptor and other signaling molecules such as Rac1 and NAD(P)H oxidase (Olivares-Reyes et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The AT1 receptor in turn transactivates EGF receptor, which leads to activation of multiple downstream effectors such as Ras-ERK and PI3-K. In this regard, caveolin-1 appears to serve a scaffold forming a large signalplex, which includes AT1 receptor, EGF receptor and other signaling molecules such as Rac1 and NAD(P)H oxidase (Olivares-Reyes et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…10 In a recent commentary, 37 the large signaling complex in hepatocyte C9 cells that was Ang II stimulated and Cav1 dependent and that contained not only Cav1 but also AT 1 R and EGF-R was referred to as a "signalplex." 38 Moreover, intactness of the microtubule and of the actin cytoskeleton systems and the presence of the actin-binding, nonreceptor tyrosine kinase cAbl, which is a substrate of cSrc and binds to Cav1, are essential for proper AT 1 R targeting into Cav1-enriched lipid rafts in VSMCs. 7,10,39 Mundy et al 40 reported that microtubules and the actin cytoskeleton are involved in trafficking, bidirectionally, of Cav1 containing vesicles ("cavicles") between the cell membrane and intracellular compartments, called caveosomes (Figure 1d).…”
Section: Caveolin and At 1 R Traffickingmentioning
confidence: 99%
“…Angiotensin receptors tend to form physical complexes with EGFR [57]. AT1r forms complexes with the C-terminal part of EGFR [58].…”
Section: Angiotensin Receptorsmentioning
confidence: 99%
“…Increased EGFR expression has profound effects on signalling pathways. High receptor density promotes its dimerization, which controls receptor endocytosis [134], which is further regulated by GPCR's [135] prominently via a mutual interaction with AT1r [57].…”
Section: Consequences Of Egfr Overexpressionmentioning
confidence: 99%